Rethinking Our Metrics: Research in the Field of Higher Education in Prison - Gould, Mary Rachel (The prison journal, 2018)
Increasing access to higher education in prison often hinges upon a series of seemingly compelling and related rationales: the reduction of recidivism, saving taxpayer dollars, and increasing safety and security (inside and outside of prisons). The purpose of this volume is to move beyond the discussion of recidivism, cost and safety and security metrics and the randomized control trial as the gold-standard for assessing the function and outcomes of higher education in prison. Instead, the collection of essays in this volume forward a more expansive way to understand why and how higher education in prison supports students. Attempting to quantify the rationale for higher education in prison based on recidivism rates, economic savings, and/or community safety statistics will never build a sustainable argument for why higher education in prison is a meaningful and potentially transformative experience for a formerly incarcerated person; in the same way that employment rates will not independently indicate why higher education is a potentially transformative experience for a student on a traditional campus. The effort to question the metrics and methodologies used to assess prison education programs and the outcomes for students as well as to provide alternative ways of evaluating the work of higher education in prison is present in each of the articles in this journal issue.